Inhibition of spikes in an array of coupled FitzHugh–Nagumo oscillators by external periodic forcing - Adomaitienė, Elena; Mykolaitis, Gytis; Bumelienė, Skaidra; Tamaševičius, Arunas (Nonlinear Analysis: Modelling and Control, 2017)
Damping of spikes in an array of coupled oscillators by injection of sinusoidal current is studied both electronically and numerically. The effect is investigated using an array consisting of thirty mean-field coupled FitzHugh–Nagumo-type oscillators. The results are considered as a possible mechanism of the deep brain stimulation used to avoid the symptoms of the Parkinson’s disease.